Risk factors for tick infestation and equine Piroplasmosis infection among draught horses in France - C. Nadal; C. Chanet; C. Delaunay; Pierre-Hugues Pitel; M. Marsot; S.I. Bonnet (Ticks and Tick-Borne Diseases)
Equine piroplasmosis, caused by the protozoan parasites Babesia caballi and Theileria equi, is endemic in Europe's Mediterranean basin, creating significant health and economic challenges for the equine sector. With no available vaccine, an eco-epidemiological approach is essential in order to identify and implement effective preventive measures. With this aim in view, we identified risk factors associated with B. caballi and T. equi infections and tick infestation for draught horses in the Auvergne-Rhône-Alpes region of France, known for its high piroplasmosis seroprevalence. During the spring of 2021, blood samples from 146 horses and ticks from both hosts and pastures were collected across 38 farms, then analysed using PCR to determine parasite prevalence. Environmental and meteorological data, along with information on management practices and individual horse characteristics, were collected on-site and from national databases. The results showed significant spatial variability in T. equi and B. caballi prevalence in horses, ranging from 25.7 % [95 % CI: 13.1 – 43.6] to 83.7 % [95 % CI: 69.8 – 92.2] and from 0 % [95 % CI: 0.0 – 26.8] to 26.5 % [95 % CI: 15.4 – 41.3], respectively. Among 1046 collected ticks, 3 % carried either a species of Babesia or Theileria and were identified as Dermacentor marginatus, Dermacentor reticulatus or Ixodes ricinus. We showed a stronger link between the environment and tick exposure for T. equi infections, while B. caballi infections were more closely associated with individual horse characteristics and management practices. Key risk factors for tick infestation included environmental conditions (temperature, rainfall, vegetation cover, altitude, etc.) and the presence of wild animals in pastures. These findings provide a valuable foundation on which to develop targeted prevention and control strategies to protect horses in enzootic regions.